Exploring Trichoderma diversity in the Western Ghats of India: phylogenetic analysis, metabolomics insights and biocontrol efficacy against Maydis Leaf Blight disease - Manzar, Nazia; Kashyap, Abhijeet Shankar; Roy, Manish; Sharma, Pawan Kumar; Srivastava, Alok Kumar (Frontiers in Microbiology, 2024)
The Western Ghats of India is recognized as one of the world’s eight “hottest hotspots” of biological diversity. Trichoderma—a well-known biocontrol agent, was explored from this hotspot. A total of 260 Trichoderma spp. isolates were studied, with 9% exhibiting strong biocontrol potential and crop growth-promoting activity. Furthermore, this study identified three novel isolates—Trichoderma caribbaeum var. caribbaeum, Trichoderma lixii, and Trichoderma brevicompactum—which are reported for the first time from the Western Ghats making a significant contribution to the field. Based on internal transcribed spacer ribosomal RNA (ITS-rRNA) and translation elongation factor 1-α (tef-1α) gene sequence analysis, molecular characterization, identified major isolates as Trichoderma koningiopsis, Trichoderma asperellum, T. caribbaeum var. caribbaeum, T. lixii, T. brevicompactum, Trichoderma atroviride, and Trichoderma erinaceum. Seed biopriming with the effective Trichoderma strain TR11 reduced the maydis leaf blight (MLB) disease index to 32.92% and improved plant growth-promoting attributes in maize. Defensive enzyme activities were increased 2.5–4.2-fold in various treatments with the TR11 isolate, along with enhanced lignification postpathogen inoculation, indicating strengthened plant defense mechanisms. The promising strain T. brevicompactum-TR11 produces secondary metabolites; among them, 5% were found to have a role in biocontrol activity such as octadecanoic acid, palmitic acid-TMS, 5-(4-nitrophenoxymethyl), furane-2-carboxaldehyde, and stearic acid-TMS, phosphoric acid-3TMS, galactopyranose, 5TMS. This study explored Trichoderma diversity in the Western Ghats of India with phylogenetic relationship, metabolomics insights, and biocontrol efficacy against MLB disease.